Perovskitas de haleto inorgânicas sob condições extremas de temperatura e pressão - Peixoto, Raul Batista (2023)
Halide perovskites have shown great potential for application in photovoltaic solar cells, light emitting diodes (LEDs) and photodetectors due to their stability and optoelectronic performance. Totally Inorganic perovskites have been seen as a solution to the instability of organic-inorganic perovskites at environmental conditions, in addition their toxicity as lead-based compoundshas been a challenge in the application of these perovskites as a commercial device. In this perspective, the method of slow evaporation of the solvent was used to obtain the inorganic perovskites Cs2NaFeCl6 and CsAgBr2, whose vibrational properties under extreme conditions of temperature and pressure were investigated employing of Raman spectroscopy. The single crystal X-ray diffraction measurement confirmed the cubic structure with space group Fm3m of the compound Cs2NaFeCl6 already known in the literature, 3 modes were found at the initial pressure 0 .18 GPa, and one of these modes not reported in the literature, and no evidence of structural phase transition was found in the range of 0.8 - 7.06 GPa confirming the great stability of its octahedral network and its complete return to the initial condition reveals its resilience. For the compound CsAgBr2 the single crystal X-ray Diffraction measurement confirmed the orthorhombic structure with space group Cmcm, reported in the literature. In the Raman spectrum at low temperatures, 7 modes were observed at 300 K and 10 modes were observed at 10 K, no evidence of structural phase transition was found, only mode resolution, indicating good thermal stability of the compound at low temperatures. In the spectrum at ambient pressure, 6 modes were observed, the measurements at high pressure reveal possible structural changes due to the appearance of modes and changes in the spectrum during the compression of the compound. A probable compound amorphization process of 2.17 GPa was also observed due to the increase in crystal disorder.